Cross-sectional study to evaluate burnout among pharmacy staff in Saudi Arabia during COVID-19 pandemic - Lobna A. Aljuffali; Munerah O. Alshabanah; Haya M. Almalag (Elsevier, 2022)
Background: Coronavirus disease 2019 (COVID-19) has placed healthcare workers, including pharmacists, at an increased risk of infection and has increased their workload, which could lead to burnout. Therefore, the present study aimed to measure the levels of burnout among hospital and community pharmacists in Saudi Arabia during the COVID-19 pandemic and to identify the risk factors associated with burnout. Methods: In the present cross-sectional study, an online survey was distributed among community and hospital (inpatient, outpatient, clinical, and administration) pharmacists in Saudi Arabia. The Copenhagen Burnout Inventory (CBI) survey was used to measure burnout levels. This 19-item survey covered three aspects: personal, work, and patient-related burnout. The survey included questions about socio-demographic factors and the major causes of psychological distress among pharmacists during the COVID-19 pandemic. Inferential statistics were used for data analysis. Results: A total of 502 pharmacists were included in the present study. Of these, 59.1% were categorized as having clinically relevant burnout levels (scores ≥ 50).Univariate analysis revealed that the burnout level was significantly higher (p < 0.05) among pharmacists who were younger, were females, had lesser years of experience, or worked in the community pharmacy. The main factors associated with high burnout levels among community pharmacists were younger age, lesser years of experience, male gender, non-Saudi nationality, and higher numbers of customers. In the COVID-19 part of the survey, burnout was found to be strongly related to the COVID-19 pandemic. Fears of getting infected or of a family member getting infected, fears of the pandemic lasting for too long, and increased working hours were factors contributing to increased burnout levels during the COVID-19 pandemic with unadjusted β of 8.336 and (95% CI 7.082-9.589, p value < 0.001). A lack of supportive work culture and sleeping disturbances were also found to be related to high burnout levels (p < 0.001). Conclusions: Pharmacy staff in Saudi Arabia were found to experience high levels of burnout. The major risk factors causing burnout included younger age, female gender, lesser years of experience, a lack of supportive work culture, sleep disturbances, worries associated with increased workload during the pandemic, fears of getting infected, and increased working hours.